Investigating the Efficiency of Zirconium Oxide Nanoparticles in Removal of Ciprofoxacin from Aqueous Environments: Pharmaceutical Science-Nanoparticle for safe for environment - Davoud Balarak; Marzieh Baniasadi; Kethineni Chandrika (International Journal of Life Science and Pharma Research, 2022)
Antibiotics as emerging contaminants are of global concern due to the development of antibiotic resistant genes potentially causing superbugs. The inefficiency of conventional purification processes in the complete removal of antibiotics increases the resistance of microorganisms in humans and the environment, hence new and low-cost technology is needed. Adsorptive materials have been extensively used for the conditioning, remediation and removal of inorganic and organic hazardous materials. Zirconium oxide is a widely used inorganic material which is chemically stable, non-toxic and not soluble in water. Thus it could be an attractive candidate for drinking water puri? cation. In this study, Zirconium Oxide Nanoparticles (ZrO2NP)has been used as the adsorbent for the possibility of removing Cipro? oxacin (CIP) from aqueous solution using the batch adsorption technique under different conditions of initial CIP concentration (25, 50, 75, 100 mg/L), adsorbent dose (0.1, 0.2, 0.3, 0.5, 0.7, 0.9 and 1 g/L) and contact time (10-150 min). The percentage of CIP adsorbed increased with increase in the mass of the adsorbent dose from 0.1 to 1 g/L. Kinetics study for sorption was evaluated using diffusion models, pseudo-first order kinetic and pseudo-second order kinetic. Results show that pseudo second-order kinetic model gave the best description for the adsorption process. The experiments showed that the highest removal rate was 96.5% under optimal conditions. The sorption of CIP on ZrO2NP was rapid during the first 30 min and the equilibrium attained within 75 min. The results suggest that ZrO2NPcould be a good candidate to remove CIP from wastewater containing different amounts of antibiotic.